SWIMMING EXERCISE STIMULATES NEURO-GENESIS IN THE SUBVENTRICULAR ZONE VIA INCREASE IN SYNAPSIN I AND NERVE GROWTH FACTOR LEVELS - C-H, Chae; Jung, S-L; An, S-H; Park, B-Y; Kim, T-W; Wang, S-W; Kim, J-H; Lee, H-C; Kim, H-T (Biology of Sport, 2014)
In this study, we investigated the effects of 8-weeks of swimming exercise on neurogenesis in the subventricular zone (SVZ) and on the levels of nerve growth factor (NGF) and synapsin I protein in the olfactory bulb (OB) of adult rats at a series of relevant time points (2 days, 1 week, 2 weeks, 4 weeks, 3 months, and 6 months). Ninety-six male Sprague Dawley rats were divided into 2 groups: (1) a control group (COG; n = 48, n = 8 for each time point) and (2) a swimming exercise group (SEG; total n = 48; n = 8 for each time point). SEG performed swimming exercise for 5 days per week over a period of 8 weeks. We found that the number of 5-bromo-2’-deoxyuridine-5’-monophosphate (BrdU)- and doublecortin (DCX)-positive cells was significantly higher in SEG than in COG at all time points (Day 2, Week 1, Week 2, Week 4, Month 3, and Month 6; p < 0.001). Furthermore, NGF and synapsin I protein levels were significantly higher in SEG on Day 2, and Weeks 1, 2, and 4 than in COG (p < 0.05 for each time point). Our findings suggest that regular swimming exercise in adult rats increases neurogenesis, neuronal survival, and neuronal maintenance in the SVZ; furthermore, swimming exercise increases the levels of NGF and synapsin I in the OB.